A Descriptive Study On Teaching-Learning Process Of Speaking At The Second Semester Of English Department Of Muhammadiyah University Of Surakarta In 2011/2012 Academic Year - Nurhayati, Fauziah (2012)
This research paper is intended to describe the teaching learning process of speaking at the second semester of English Department of Muhammadiyah University of Surakarta. It is conducted to describe the method used by the lecturer of speaking 2 and the strength also the weakness of its method. The data are taken from all elements of teaching-learning process committed by the lecturer and the students and other sources such as information, events, student teacher interactions, the process of teaching and learning, and the materials. The methods of collecting data are interview, document and observation. This research is descriptive qualitative which does not include any calculation or statistic procedure. The result of the research shows that the method used by the lecturer is direct method with its principles. It used some strategies to apply direct method perfectly like role play, games, sharing, discussion and song. The use of direct method can not effective because there is Indonesian language about 10% in the teaching learning process of speaking 2. The strengths of the method are it can make the students are more involved, active, familiar with the target language and have more confidence to speaking up. Whereas the weaknesses of using direct method are about difficulty of controlling class, it is rather difficult to be applied in large class; the student that has less skill can not follow the other, and needs many times because most of students need long time to understand.